Accurate Wavenumber Measurement in High Resolution Stimulated Raman Spectroscopy (SRS) by Using an Infrared Standard. ν1 Fundamental of 12CH4. Issue 1 (1992) - Santos, J.; Cancio, P.; Domenech, J. L.; Rodriguez, J.; Bermejo, D.
Abstract : A new set of wavenumbers for the Stimulated Raman Spectrum (SRS) of theν 1 band of 12 CH4 is presented using the Infrared (IR) absorption spectrum of the P 10 component ofν 3 of the same molecule as a wavenumbers standard. An estimation of the Stark shift due to the pump laser field is experimentally deduced what allows to extrapolate the measured wavenumbers to zero field amplitude. A careful discussion about the main possible error sources and how to cope with them is also included. The absolute accuracy of the wavenumbers set presented here is believed to be at least one order of magnitude better as compared with previous measurement.